Reluctant altruism and peer pressure in charitable giving - Diane Reyniers; Richa Bhalla (Judgment and Decision Making, 2013)
Subjects donate individually (control group) or in pairs (treatment group). Those in pairs reveal their donation decision to each other. Average donations in the treatment group are significantly higher than in the control group. Paired subjects have the opportunity to revise their donation decision after discussion. Pair members shift toward each others’ initial decisions. Subjects are happier with their decision when their donations are larger, but those in pairs are less happy, controlling for amount donated. These findings suggest reluctant altruism due to peer pressure in charitable giving.